Justification of Constructing Rijeka-Zagreb Motorway Section for the Development of the Port of Rijeka - Huzjan, Boris; Kregar, Karolina (Promet - Traffic&Transportation, 2006)
The article describes the significance of the Rijeka-Zagrebmotorway for the development of the Port of Rijeka, as well asits significance in the European road network and the networkof state motorways. It gives a short historic overview of thephase construction of the Rijeka-Zagreb motorway per sectionsand years of completion, and the most important parametersare mentioned that influence the justification of the upgradingof the motorway section to full transversal profile.Since 'traffic' is one of the key components of developmentand necessary for all the aspects of human activities, the completionof a safe, reliable and fast traffic connection of the Croatiancapital with the biggest Croatian port represents the keyfactor of the Strategy of traffic development of the Republic ofCroatia.Besides, the Rijeka-Zagreb motorway represents the backboneof the Croatian motorway network, since it integrates theCroatian space connecting it with the European traffic corridors.Thus, new possibilities are opened to the national economy,mainly tourism and port traffic, and bringing direct benefits.Therefore, the greatest significance of the construction i. e.upgrading of this motorway lies precisely in raising the qualityof traffic service regarding road connection, but also in a widertraffic sense.